Análise dos modais de transporte no Vale do Jaguari/RS e os desafios da mobilidade dos produtores de frutas e hortaliças - Silva, Ricardo Vieira da (2020)
Geographical science seeks to describe, analyze and understand geographical space. Its need is due to the interrelationships and human interactions. By appropriating the environment, man begins to produce both goods and services and objects in order to meet his needs. Consequently, by interacting with the environment, society, as a rule, starts to be impacted by the conditions/restrictions it presents. In this context, the present study had as a general objective, to characterize the influence of geomorphological and structural elements that condition (limit/potentialise) the mobility of horticulturalists in the municipalities of Santiago, Nova Esperança do Sul and Jaguari, members of the Jaguari Valley, Rio Grande do Sul. A series of computational tools contained in the Geographic Information Systems were applied, with emphasis on the free software QGIS version 3.4 LTR "Madeira", where a series of routines and spatial analyses were carried out in order to better understand the study area. Adding to the fieldwork done in September 2018/2019, they are essential for a better understanding of the processes working on rural roads. As for the results reported, initially an analysis of horticultural production was made, as a way to obtain subsidies that would justify the demand for transportation. It was observed that in the period of 12 years between 2006 and 2018, there was an increase of 4.76% in horticultural production, from 4,667.00 to 4,889.00 tons, between 2006 and 2018, thus justifying the need for a modal capable of meeting such needs. On the other hand, it was observed that almost 80% of the roads in the respective municipalities are unpaved, suffering from holes, erosion, absence of drainage, etc. Geomorphological analyses, on the other hand, show that they affect, restrict/condition the trafficability of rural roads, affecting mobility both for agricultural production, especially horticultural production, and for those who indirectly depend on the road system as a whole.